The researcher as detective: Another way of looking at professions and organizations. Issue 1 (5th February 2019) - Sherer, Peter D
Abstract: How do we meet the challenge of exploring phenomenon in the world around us while staying true to the importance that we, as academics, place on theory building and testing? I argue for taking a detective-like approach in conducting such research on professions and organizations, particularly as it relates to archival and historical research. In so doing, we look at the world around us for generating ideas on what to study as opposed to filling gaps gleaned from reading academic articles, serendipitously find data sources, go from scattered pieces of data to outcroppings, get to coherence through a mixed methods approach of combining two or more methods, and utilize professionals in organizations to verify and potentially enrich our theoretical arguments and also to gain further insight into our findings. A detective-like approach is especially valuable when the theory and data do not directly follow from an extant academic gap, and where the evidence is circumstantial rather than determinative, lacking the 'smoking gun' that we see in exemplary quantitative work. This detective-like approach can help us to challenge and advance our extant theories and, at times, support the development of new theoretical arguments.